Ответы и объяснения

2012-02-11T14:32:59+00:00

(7х+4)+х=15            (х+2)=6-2х      +2х

7х+4+х=15               х+2+2х=6

8Х+4=15                   3х+2=6

8Х=15-4                    3х=6-2

8х=11                        3х=4

х=11:8                       х=4:3

х=1 3/8                      х=1 1/3

 

 

Лучший Ответ!
2012-02-11T14:59:23+00:00

(7х+4)+х=15  (х+2)=6-2х  
7х+4+х=15     х+2+2х=6
8Х+4=15        3х+2=6
8Х=15-4        3х=6-2
8х=11            3х=4
х=11:8        х=4:3
х=1 3/8      х=1 1/3